Beyond Religions: The Serenity of Fasting in Buddhism and its Impact on Mental Well-being - Tiya Fitriani; Pupule Seelananda (Subhasita: Journal of Buddhist and Religious Studies, 2023)
This research delves into the practice of fasting in Buddhism, specifically focusing on Vihara Karuna Mukti in Bandung, Indonesia, and its implications for mental well-being. Fasting is a religious practice observed in various faiths, including Buddhism, and this study aims to explore its significance within this particular context. Using a descriptive qualitative research approach, the author investigates the practice of fasting in Buddhism, employing data collection techniques such as observation, interviews, and documentation. The findings reveal that at Vihara Karuna Mukti, fasting is observed on specific dates according to the Buddhist calendar, including the 1st, 8th, 15th, and 22nd days of the lunar month, as well as by the monks who fast daily. Buddhists are permitted to consume food from morning until noon, approximately from 7:00 AM to 12:00 PM, after which they abstain from eating until the following day. However, they are still allowed to drink water during the fasting period. Additionally, adherence to Atthasila, which encompasses eight virtues, is expected during fasting. The study concludes that the practice of fasting among Buddhists at Vihara Karuna Mukti holds implications for mental well-being when approached with sincerity. Fasting aids in cultivating self-control, promoting a sense of inner calmness, and nurturing virtues such as patience and honesty. It highlights the transformative potential of fasting as a means to enhance mental and spiritual aspects of life beyond religious boundaries. Overall, this research sheds light on the serenity of fasting in Buddhism and its positive impact on mental well-being, providing valuable insights into the interplay between religious practices and personal growth within the context of Vihara Karuna Mukti.